Studies of quantum interference effects in iron-nickel-silicon-boron amorphous alloys - Wang, Pu (University of Ottawa (Canada), 2004)
The purpose of this thesis is to study the temperature dependence of the electrical resistivity of the pseudo-binary (FexNi 1-x)77Si10B13 alloy system. The high precision four-wire electrical resistivity measuring method is used to obtain the resistance data of the samples from 2.1 K to 290 K. It is shown that the combination of quantum corrections, magnetic, and the thermal electron-phonon scattering contributions account for the temperature dependence of the electrical resistivity over the entire temperature range. The electron-electron interaction and the weak localization effects are dominant at low temperatures. At high temperatures, the mechanism of the electrical resistivity depends on the magnetic state of the alloy. When the sample is paramagnetic, the magnetic contribution is negligibly small and can be ignored in comparison to the contribution due to the structure factor. The magnetic contribution shows up at high temperatures at which the sample is ferromagnetic. The weak localization effects and electron-phonon scattering persist in high-temperature range. A good agreement between the fits and the experimental data are obtained in this study. The existing theories account well for the complexity of the temperature dependence of the electrical resistivity.
Keywords: Physics, Condensed Matter.; Engineering, Materials Science.